Oriented polylactic acid nanofiber membrane with synergistically controllable topological structure and piezoelectric property as well as preparation method and application of oriented polylactic acid nanofiber membrane
Through high-voltage electrospinning technology and organic reagent treatment, polylactic acid nanofiber membranes with controllable topological structure and piezoelectric properties were prepared, which solved the problem of insufficient controllability of fiber membranes in the topological structure and piezoelectric properties in the prior art, and achieved efficient application of biological tissue regeneration.
Patent Information
- Application Number
- CN202411843091.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
AI Technical Summary
The existing polylactic fiber membranes have shortcomings in the controllability of topological structure and piezoelectric properties, and it is difficult to achieve customized topological structures and piezoelectric outputs, which limits its application in biological tissue engineering.
By controlling the time of fiber treatment of organic reagents, oriented polylactic acid nanofiber membranes are prepared by high-voltage electrospinning technology, and impregnation is used to regulate the topological structure and piezoelectric properties of the fiber membrane.
The synergistic control of the topological structure and piezoelectric properties of polylactic acid nanofiber membrane is achieved, the piezoelectric properties of the fiber membrane are improved, and the output current is significantly enhanced, which is suitable for promoting biological tissue or nerve regeneration.
Smart Images

Figure CN119663551A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of biomaterial preparation, and particularly relates to an oriented polylactic acid nanofiber membrane with synergistically controllable topological structure and piezoelectric properties, and a preparation method and application thereof. Background Art
[0002] Polylactic acid is a biodegradable biomedical material recognized by the U.S. Food and Drug Administration. Polylactic acid has the advantages of soft texture, mild processing conditions, and good biocompatibility. Current studies have found that polylactic acid will be endowed with piezoelectric effect after special treatment. The application forms of polylactic acid are mainly thin films and fiber membranes. Common methods for achieving piezoelectricity include heating and stretching, electrospinning, template infiltration, etc. Among them, electrospinning technology is a simple method for preparing polylactic acid membranes. The electric field and high-speed rotating roller receiver can obtain highly oriented polylactic acid fiber membranes, so that their dipoles are arranged parallel to the direction of the molecular chain, thereby generating shear piezoelectricity, which further increases the added value of polylactic acid. The excellent degradability and piezoelectricity make polylactic acid more likely to become implantable bioelectronics, especially for the in vivo treatment and power generation of polylactic acid. On the other hand, as a medical degradable material commonly used in tissue engineering, the surface topological structure of polylactic acid fiber provides physical clues for tissue regeneration and functional recovery. However, the surface topology and piezoelectric controllability of polylactic acid fiber are still a difficult problem. The customization of topological structure and piezoelectric output will further promote the application of polylactic acid fiber in biological tissue engineering, such as degradable medical biomaterials, used to promote biological tissue or nerve regeneration. Summary of the invention
[0003] The present invention prepares an oriented polylactic acid nanofiber membrane with synergistically controllable topological structure and piezoelectric properties, and a preparation method and application thereof, and can achieve synergistic control of topological structure and piezoelectricity by controlling the fiber treatment time with an organic reagent.
[0004] The first aspect of the present invention provides a method for preparing an oriented polylactic acid nanofiber membrane with a topological structure and piezoelectric properties that are synergistically controllable, the preparation method comprising the following steps:
[0005] S1. adding L-polylactic acid and polyethylene oxide to a first solvent to obtain a spinning solution;
[0006] S2. electrospinning the spinning solution to obtain an oriented nanofiber membrane;
[0007] S3. The oriented nanofiber membrane is immersed in a second solvent for a preset time to obtain an oriented polylactic acid nanofiber membrane having a predetermined topological structure and preset piezoelectric properties, wherein the second solvent is ethyl acetate or N,N-dimethylamide.
[0008] In some embodiments, the first solvent is trifluoroethanol.
[0009] In some embodiments, in step S1, for every 10 mL of the first solvent, the amount of L-polylactic acid used is 0.25 g-0.45 g, and the amount of polyethylene oxide used is 0.05 g-0.25 g.
[0010] In some embodiments, step S2 is specifically as follows: using a high-voltage electrospinning device to electrospin the spinning solution into an oriented nanofiber membrane, the spinning solution pushing rate of the high-voltage electrospinning device is 0.5 mL / h, the voltage is 7 to 10 kV, and a roller wrapped with aluminum foil with a rotation speed of 2000 r / min is used to receive the fibers to collect the oriented nanofiber membrane.
[0011] In some embodiments, in step S3, the preset time is 10-30 minutes.
[0012] In some embodiments, in step S3, the preset time is set according to preset piezoelectric performance requirements and the type of the second solvent.
[0013] In some embodiments, the second solvent is ethyl acetate, and the preset time is 10 minutes.
[0014] In some embodiments, the second solvent is N,N-dimethylformamide, and the preset time is 20 minutes.
[0015] The second aspect of the present invention provides an oriented polylactic acid nanofiber membrane prepared according to the above preparation method.
[0016] The third aspect of the present invention provides a use of the above-mentioned oriented polylactic acid nanofiber membrane in the preparation of a degradable medical biomaterial, wherein the degradable medical biomaterial is used to promote the regeneration of biological tissues or nerves.
[0017] The oriented polylactic acid nanofiber membrane with coordinated controllable topological structure and piezoelectric properties and its preparation method and application according to the embodiment of the present invention have the following advantages:
[0018] Firstly, high-voltage electrospinning technology was used to collect fibers using a roller connected to a ground wire, and highly oriented ultrafine polylactic acid nanofibers were collected. Then, ethyl acetate or N,N-dimethylamide reagent was used to soak the oriented fiber membrane. Different reagent treatment times will reshape the surface morphology of the oriented polylactic acid fiber. On the other hand, the crystallinity of the polylactic acid membrane will also have an impact, thereby further regulating the piezoelectric properties of the oriented polylactic acid fiber. The study found that N,N-dimethylamide treatment will improve the piezoelectric properties of polylactic acid fibers. When the treatment time is 20 minutes, the piezoelectricity of the polylactic acid fiber is significantly enhanced, and the output current is 7.58*10 -5 ±7.44*10 -6A. Ethyl acetate treatment also enhances the piezoelectric properties of polylactic acid fibers. When the treatment time is 10 min, the piezoelectric effect is the best, and the output current is 1.07*10 -9 ±1.05*10 -12 A. In general, the surface topology and piezoelectric properties of PLA fibers can be indirectly regulated by controlling the immersion time of ethyl acetate and N,N-dimethylamide reagents. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The figures are scanning electron microscope images of untreated polylactic acid fibers (sample of Example 1) and oriented polylactic acid fibers treated with ethyl acetate for 10 min, 20 min, and 30 min (samples of Examples 2-4) and electrical signal output images under a pressure of 2N;
[0020] Figure 2 It is a graph of the output current value of electrical signals of untreated polylactic acid fibers (sample of Example 1) and oriented polylactic acid fibers treated with ethyl acetate for 10 min, 20 min, and 30 min (samples of Examples 2-4) under a pressure of 2N;
[0021] Figure 3 The scanning electron microscope images of untreated polylactic acid fibers (sample of Example 1) and oriented polylactic acid fibers treated with N,N-dimethylamide for 10 min, 20 min, and 30 min (samples of Examples 5-7) and the electrical signal output images under a pressure of 2N;
[0022] Figure 4 It is a graph of the electrical signal output current values of untreated polylactic acid fibers (sample of Example 1) and oriented polylactic acid fibers treated with N,N-dimethylamide for 10 min, 20 min, and 30 min (samples of Examples 5-7) under a pressure of 2N. DETAILED DESCRIPTION
[0023] The present invention will be further described below in conjunction with specific implementation steps. It should be understood that these implementations are only used to illustrate the present invention and are not used to limit the scope of the present invention. In addition, it should be understood that after reading the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent situations also fall within the scope limited by the appended claims of the application.
[0024] L-polylactic acid (Mw 100,000, Jinan Daigang Bioengineering Co., Ltd.)
[0025] Polyethylene oxide (Mr = 5000 kDa, Alfa Aesar)
[0026] Trifluoroethanol (T819391, MacLean)
[0027] Ethyl acetate (E809174, Maclean)
[0028] N,N-dimethylamide (D112004, Aladdin)
[0029] Example 1
[0030] At room temperature, 0.45g PLLA (levorotatory polylactic acid) and 0.05g PEO (polyethylene oxide Mr = 5000kDa) were added to 10mL TFE (trifluoroethanol) and stirred to dissolve at room temperature overnight. The polylactic acid solution was electrospun into nanofibers using a high-voltage electrospinning device, and the solution pushing rate was controlled to be 0.5mL / h, and the voltage was 7kV. The fiber membrane was received by a high-speed rotating roller wrapped in aluminum foil, and the roller speed was 2000r / min. The oriented nanofiber membrane was collected and placed in a vacuum drying oven for 24h.
[0031] Example 2
[0032] At room temperature, 0.45g PLLA (levorotatory polylactic acid) and 0.05g PEO (polyethylene oxide Mr = 5000kDa) were added to 10mL TFE (trifluoroethanol) and stirred to dissolve at room temperature overnight. The polylactic acid solution was electrospun into nanofibers using a high-voltage electrospinning device, and the solution pushing rate was controlled to be 0.5mL / h, and the voltage was 8kV. The fiber membrane was received by a high-speed rotating roller wrapped in aluminum foil, and the roller speed was 2000r / min. The oriented fiber membrane was collected and placed in a vacuum drying oven for 24h.
[0033] The dried membrane was cut into 2cm×2cm films, the fiber membrane was fixed with stainless steel clips, the oriented fiber membrane was completely immersed in ethyl acetate, and the oriented fiber membrane was taken out after immersion treatment for 10 minutes to obtain an oriented polylactic acid nanofiber membrane with a predetermined topological structure and preset piezoelectric properties.
[0034] Example 3
[0035] At room temperature, 0.9g PLLA (levorotatory polylactic acid) and 0.1g PEO (polyethylene oxide Mr = 5000kDa) were added to 20mL TFE (trifluoroethanol) and stirred to dissolve at room temperature overnight. The polylactic acid solution was electrospun into nanofibers using a high-voltage electrospinning device, and the solution pushing rate was controlled to be 0.5mL / h, and the voltage was 7kV. The fiber membrane was received by a high-speed rotating roller wrapped in aluminum foil, and the roller speed was 2000r / min. The oriented fiber membrane was collected and placed in a vacuum drying oven for 24h.
[0036] The dried membrane was cut into 2cm×2cm films, the fiber membrane was fixed with stainless steel clips, the oriented fiber membrane was completely immersed in ethyl acetate, and the oriented fiber membrane was taken out after immersion for 20 minutes to obtain an oriented polylactic acid nanofiber membrane with a predetermined topological structure and preset piezoelectric properties.
[0037] Example 4
[0038] Under room temperature, 0.9g PLLA (levorotatory polylactic acid) and 0.1g PEO (polyethylene oxide Mr = 5000kDa) were added to 20mL TFE (trifluoroethanol) and stirred to dissolve at room temperature overnight. The polylactic acid solution was electrospun into nanofibers using a high-voltage electrospinning device, and the solution pushing rate was controlled to be 0.5mL / h, and the voltage was 7kV. The fiber membrane was received by a high-speed rotating roller wrapped in aluminum foil, and the roller speed was 2000r / min. The oriented fiber membrane was collected and placed in a vacuum drying oven for 24h.
[0039] The dried membrane was cut into 2cm×2cm films, the fiber membrane was fixed with stainless steel clips, the oriented fiber membrane was completely immersed in ethyl acetate, and the oriented fiber membrane was taken out after immersion for 30 minutes to obtain an oriented polylactic acid nanofiber membrane with a predetermined topological structure and preset piezoelectric properties.
[0040] Example 5
[0041] Under room temperature, 0.9g PLLA (levorotatory polylactic acid) and 0.1g PEO (polyethylene oxide Mr = 5000kDa) were added to 20mL TFE (trifluoroethanol) and stirred to dissolve at room temperature overnight. The polylactic acid solution was electrospun into nanofibers using a high-voltage electrospinning device, and the solution pushing rate was controlled to be 0.5mL / h, and the voltage was 7kV. The fiber membrane was received by a high-speed rotating roller wrapped in aluminum foil, and the roller speed was 2000r / min. The oriented fiber membrane was collected and placed in a vacuum drying oven for 24h.
[0042] The dried membrane was cut into 2cm×2cm films, the fiber membrane was fixed with stainless steel clips, and the oriented fiber membrane was completely immersed in N,N-dimethylamide. After immersion treatment for 10 minutes, the oriented fiber membrane was taken out to obtain an oriented polylactic acid nanofiber membrane with a predetermined topological structure and preset piezoelectric properties.
[0043] Example 6
[0044] Under room temperature, 0.9g PLLA (levorotatory polylactic acid) and 0.1g PEO (polyethylene oxide Mr = 5000kDa) were added to 20mL TFE (trifluoroethanol) and stirred to dissolve at room temperature overnight. The polylactic acid solution was electrospun into nanofibers using a high-voltage electrospinning device, and the solution pushing rate was controlled to be 0.5mL / h, and the voltage was 7kV. The fiber membrane was received by a high-speed rotating roller wrapped in aluminum foil, and the roller speed was 2000r / min. The oriented fiber membrane was collected and placed in a vacuum drying oven for 24h.
[0045] The dried membrane was cut into 2cm×2cm films, the fiber membrane was fixed with stainless steel clips, and the oriented fiber membrane was completely immersed in N,N-dimethylamide. After immersion for 20 minutes, the oriented fiber membrane was taken out to obtain an oriented polylactic acid nanofiber membrane with a predetermined topological structure and preset piezoelectric properties.
[0046] Example 7
[0047] Under room temperature, 0.9g PLLA (levorotatory polylactic acid) and 0.1g PEO (polyethylene oxide Mr = 5000kDa) were added to 20mL TFE (trifluoroethanol) and stirred to dissolve at room temperature overnight. The polylactic acid solution was electrospun into nanofibers using a high-voltage electrospinning device, and the solution pushing rate was controlled to be 0.5mL / h, and the voltage was 7kV. The fiber membrane was received by a high-speed rotating roller wrapped in aluminum foil, and the roller speed was 2000r / min. The oriented fiber membrane was collected and placed in a vacuum drying oven for 24h.
[0048] The dried membrane was cut into 2cm×2cm films, the fiber membrane was fixed with stainless steel clips, and the oriented fiber membrane was completely immersed in N,N-dimethylamide. After immersion for 30 minutes, the oriented fiber membrane was taken out to obtain an oriented polylactic acid nanofiber membrane with a predetermined topological structure and preset piezoelectric properties.
[0049] Test Case
[0050] The samples of Examples 1-7 were placed between two glass sheets connected to two copper electrodes (ensuring that both ends of the film were connected to the two copper electrodes respectively), a force of 2N was applied using a pressure gauge, and the piezoelectricity was tested using an electrochemical workstation.
[0051] The electron microscope images of the samples of Examples 1-4 and the electrical signal output images under 2N pressure are shown in FIG. Figure 1 As shown. Figure 1 It can be seen that treating the oriented nanofiber membrane with ethyl acetate will further change the surface topology of the oriented nanofiber membrane and improve its piezoelectric properties.
[0052] The output current of the sample of Example 1 (untreated oriented nanofiber membrane) is 1.24*10-12 ±1.16*10 -13 A.
[0053] The electrical signal output current of the sample in Example 2 (the sample treated with ethyl acetate for 10 min) is 1.07*10 -9 ±1.05*10 -12 A. The piezoelectric performance of the fiber membrane treated with ethyl acetate for 10 min was the highest compared with that of the fiber membrane not treated with ethyl acetate.
[0054] Example 3 sample (sample treated with ethyl acetate for 20 min) electrical signal output current is 2.37*10 -10 ±6.75*10 -12 A. The piezoelectric properties of the fiber membrane treated with ethyl acetate for 20 min were significantly improved compared with the fiber membrane not treated with ethyl acetate.
[0055] Example 4 sample (30min ethyl acetate treatment sample) electrical signal output current is 1.97*10 -10 ±4.02*10 -12 A. The piezoelectric properties of the fiber membrane treated with ethyl acetate for 30 min were improved compared with the fiber membrane not treated with ethyl acetate.
[0056] The electrical signal output current of the sample in Example 5 (sample treated with N-dimethylamide for 10 min) is 9.31*10 -10 ±1.16*10 -11 A. The piezoelectric properties of the fiber membrane treated with N, N-dimethylamide for 10 min are slightly improved compared with the fiber membrane not treated with N, N-dimethylamide.
[0057] The electrical signal output current of the sample in Example 6 (sample treated with N-dimethylamide for 20 min) is 7.58*10 -5 ±7.44*10 -6 A. The piezoelectric performance of the fiber membrane treated with N, N-dimethylamide for 20 min was improved to the optimal state compared with the fiber membrane not treated with N, N-dimethylamide.
[0058] The electrical signal output current of the sample in Example 7 (sample treated with N-dimethylamide for 30 min) is 8.57*10 -11 ±1.34*10 -11 A. The piezoelectric properties of the fiber membrane treated with N, N-dimethylamide for 30 min were improved compared with the fiber membrane not treated with N, N-dimethylamide.
[0059] The oriented polylactic acid nanofiber membrane with coordinated controllable topological structure and piezoelectric properties and the preparation method and application thereof according to the embodiment of the present invention have at least one of the following advantages:
[0060] The oriented polylactic acid nanofiber membrane with coordinated controllable topological structure and piezoelectric properties and its preparation method and application according to the embodiment of the present invention have the following advantages:
[0061] Firstly, high-voltage electrospinning technology was used to collect fibers using a roller connected to a ground wire, and highly oriented ultrafine polylactic acid nanofibers were collected. Then, ethyl acetate or N,N-dimethylamide reagent was used to soak the oriented fiber membrane. Different reagent treatment times will reshape the surface morphology of the oriented polylactic acid fiber. On the other hand, the crystallinity of the polylactic acid membrane will also have an impact, thereby further regulating the piezoelectric properties of the oriented polylactic acid fiber. The study found that N,N-dimethylamide treatment will improve the piezoelectric properties of polylactic acid fibers. When the treatment time is 20 minutes, the piezoelectricity of the polylactic acid fiber is significantly enhanced, and the output current is 7.58*10 -5 ±7.44*10 -6 A. Ethyl acetate treatment also enhances the piezoelectric properties of polylactic acid fibers. When the treatment time is 10 min, the piezoelectric effect is the best, and the output current is 1.07*10 -9 ±1.05*10 -12 A. In general, the surface topology and piezoelectric properties of PLA fibers can be indirectly regulated by controlling the immersion time of ethyl acetate and N,N-dimethylamide reagents.
Claims
1. A method for preparing an oriented polylactic acid nanofiber membrane with synergistically controllable topological structure and piezoelectric properties, characterized in that: The preparation method comprises the following steps: S1. adding L-polylactic acid and polyethylene oxide to a first solvent to obtain a spinning solution; S2. electrospinning the spinning solution to obtain an oriented nanofiber membrane; S3. The oriented nanofiber membrane is immersed in a second solvent for a preset time to obtain an oriented polylactic acid nanofiber membrane having a predetermined topological structure and preset piezoelectric properties, wherein the second solvent is ethyl acetate or N,N-dimethylamide.
2. The preparation method according to claim 1, characterized in that: The first solvent is trifluoroethanol.
3. The preparation method according to claim 1, characterized in that: In step S1, for every 10 mL of the first solvent, the amount of L-polylactic acid used is 0.25 g-0.45 g, and the amount of polyethylene oxide used is 0.05 g-0.25 g.
4. The preparation method according to claim 1, characterized in that: Step S2 is specifically as follows: using a high-voltage electrospinning device to electrospin the spinning solution into an oriented nanofiber membrane, the spinning solution pushing rate of the high-voltage electrospinning device is 0.5mL / h, the voltage is 7-10kV, and a roller wrapped with aluminum foil with a rotation speed of 2000r / min is used to receive the fibers to collect the oriented nanofiber membrane.
5. The preparation method according to claim 1, characterized in that: In step S3, the preset time is 10-30 minutes.
6. The preparation method according to claim 1, characterized in that: In step S3, the preset time is set according to preset piezoelectric performance requirements and the type of the second solvent.
7. The preparation method according to claim 1, characterized in that: The second solvent is ethyl acetate, and the preset time is 10 minutes.
8. The preparation method according to claim 1, characterized in that: The second solvent is N,N-dimethylformamide, and the preset time is 20 minutes.
9. An oriented polylactic acid nanofiber membrane prepared according to the preparation method according to any one of claims 1 to 8.
10. Use of the oriented polylactic acid nanofiber membrane according to claim 9 in the preparation of a degradable medical biomaterial, wherein the degradable medical biomaterial is used to promote biological tissue or nerve regeneration.
Citation Information
Patent Citations
Oxide toughened porous lead zirconate titanate piezoelectric ceramic preparation method
CN103739285A
Preparation method of polylactic acid film
CN105733000A
Preparation method of P (VDF-TrFE) dendritic micro-nano fiber piezoelectric film
CN112481832A
Method for rapidly inducing phase change from alpha to gamma of polyvinylidene fluoride film
CN114409944A
Micro-nano topological structure PLLA superfine fiber material as well as preparation method and application thereof
CN116065256A